2011
DOI: 10.1016/j.jchemneu.2011.05.006
|View full text |Cite
|
Sign up to set email alerts
|

From progenitors to integrated neurons: Role of neurotransmitters in adult olfactory neurogenesis

Abstract: Adult neurogenesis is due to the persistence of pools of constitutive stem cells able to give rise to a progeny of proliferating progenitors. In rodents, adult neurogenic niches have been found in the subventricular zone (SVZ) along the lateral ventricles and in the subgranular zone of the dentate gyrus in the hippocampus. SVZ progenitors undergo a unique process of tangential migration from the lateral ventricle to the olfactory bulb (OB) where they differentiate mainly into GABAergic interneurons in the gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 146 publications
(255 reference statements)
0
25
0
Order By: Relevance
“…20 Many studies have suggested 21 that the areas of the mammalian brain that are particularly specialized to produce proliferating neuroprogenitor cells are the subgranular layer of the dentate gyrus (DG) in the hippocampus, 22 and the subventricular zone of the lateral ventricle. 23 The process of neurogenesis may be important in this acute TBI model where it can readily be seen after 4 weeks of follow-up that the neurological performance of the mice is improving; at the same time, the size of the cortical lesion is increasing. 12 In this report, we describe improvements in learning and memory in mice with severe CCI-TBI treated either one or three times with daily tLLLT.…”
Section: Introductionmentioning
confidence: 99%
“…20 Many studies have suggested 21 that the areas of the mammalian brain that are particularly specialized to produce proliferating neuroprogenitor cells are the subgranular layer of the dentate gyrus (DG) in the hippocampus, 22 and the subventricular zone of the lateral ventricle. 23 The process of neurogenesis may be important in this acute TBI model where it can readily be seen after 4 weeks of follow-up that the neurological performance of the mice is improving; at the same time, the size of the cortical lesion is increasing. 12 In this report, we describe improvements in learning and memory in mice with severe CCI-TBI treated either one or three times with daily tLLLT.…”
Section: Introductionmentioning
confidence: 99%
“…In adult animals, the presence of NA is required for the modulation in the OB of electrophysiological responses associated with olfactory learning (Gray et al, 1986), for longlasting suppression of odor responses after pairing locus ceruleus stimulation with odor presentation (Shea et al, 2008), for spontaneous discriminations (Mandairon et al, 2008a) and short-term olfactory memory (Veyrac et al, 2007(Veyrac et al, , 2009). Interestingly, olfactory enrichment stimulates the noradrenergic system (Veyrac et al, 2009;Rey et al, 2012) and NA is a positive modulator of newborn neuron survival (Bauer et al, 2003;Bovetti et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It was proposed that, in addition to their classical role in synaptic transmission, neurotransmitters (NTs) have been proposed to play functional roles both during neurogenesis and during adult life (Buznikov et al, 1996;Biagioni et al, 2002;Karczmar, 2007;Bovetti et al, 2011;Young et al, 2011;Abreu-Villaça et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, NTs appear to be "old" molecules that are present in many organisms and that participate in signaling mechanisms that control various cellular functions such as proliferation and migration. Their role in neurogenesis has been proposed on the basis of their early appearance during development, which extends well into the advanced stages of synaptogenesis (Bovetti et al, 2011;Young et al, 2011).…”
Section: Introductionmentioning
confidence: 99%